2016
DOI: 10.1109/tasc.2016.2530696
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Candidate Architectures for Future Distributed Propulsion Aircraft

Abstract: This version is available at https://strathprints.strath.ac.uk/55472/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 13 publications
0
44
0
Order By: Relevance
“…As a design requirement for the PMAD components the rated voltage of the electric propulsion system is needed. Vratny et al [28] and Jones et al [36] prove that a system voltage of 3 kV (DC) leads to the highest efficiency for all electric demands, which is chosen for the simulation. Voltage variations are handled by the converters and inverters.…”
Section: Electric Propulsion Componentsmentioning
confidence: 99%
“…As a design requirement for the PMAD components the rated voltage of the electric propulsion system is needed. Vratny et al [28] and Jones et al [36] prove that a system voltage of 3 kV (DC) leads to the highest efficiency for all electric demands, which is chosen for the simulation. Voltage variations are handled by the converters and inverters.…”
Section: Electric Propulsion Componentsmentioning
confidence: 99%
“…It also eliminates the need for synchronizing the AC generator to the AC distribution system. However, on the downside, it requires addition conversion units on both generator and motor ends in turboelectric application [183]. In a study performed on a non-cryogenic turboelectric configuration [107], three different microgrid type electrical system architectures, namely DC distribution, AC synchronous distribution, and hybrid of both AC and DC, were considered to evaluate mass and efficiency performance metrics.…”
Section: High Voltage Architecture and Protectionmentioning
confidence: 99%
“…Moreover, there is also subtle impact from the operating frequency on the system loss that makes an ideal choice of 800 Hz for this design. In a quantitative assessment study by Jones et al [183] on a cryogenically cooled TeDP configuration AC system showed better performance over DC and AC-DC hybrid systems for weight and efficiency parameters. However, controllability is a major issue for an AC system architecture.…”
mentioning
confidence: 97%
“…The required thermal management system for a chosen aero-electrical power system may have significant negative impact on performance (weight and efficiency) 58 . There may also be a limitation on where devices can be located if there is risk of the heat transfer from devices interfering with or causing damage to surrounding components.…”
Section: G Thermal Constraintsmentioning
confidence: 99%